[A selection of photographs and illustrations from the Church Missionary Society collection of lives of missionaries] - Church Mission Society; Adam Matthew Digital (Adam Matthew Digital, 2007)
Electronic reproduction of illustrations from the Church Mission Society collection of the lives of the missionaries. Includes images of missionary work in Africa, South Asia, India, Kashmir, Asia, China, Middle East, Persia, Iran, Australasia, New Zealand, and prominent figures such as Samuel Crowther and Rewi Maniapoto